Observation of hexagonal nuclei in the once melt-quenched Ge2Sb2Te5 phase change contact dimensions - Youm, Min Soo; Kim, Yong Tae; Sung, Man Young (AMER INST PHYSICS, 2007)
The microstructures of once melt-quenched Ge2Sb2Te5 (GST) phase change contact dimensions are directly investigated with high resolution transmission electron microscopy (HR-TEM) by applying reset pulse of 7-13 V. The ovonic threshold switching voltage is decreased from 4.1 to 2.8 V when the as-deposited GST cells are once melt quenched by 10 V. HR-TEM reveals that there are hexagonal nuclei in the once melt-quenched GST and the GST can be partially left in not the amorphous but the crystalline state when the molten GST is not swiftly quenched, which is an origin of the switching failure. (C) 2007 American Institute of Physics.
Keywords: LASER-INDUCED CRYSTALLIZATION; THIN-FILMS; CRYSTAL-STRUCTURE; NUCLEATION; GETE